Drosophila yakuba mayottensis, a new model for the study of incipient ecological speciation. Issue 1 (2nd January 2017) - Yassin, Amir
ABSTRACT: A full understanding of how ecological factors drive the fixation of genetic changes during speciation is obscured by the lack of appropriate models with clear natural history and powerful genetic toolkits. In a recent study, we described an early stage of ecological speciation in a population of the generalist species Drosophila yakuba ( melanogaster subgroup) on the island of Mayotte (Indian Ocean). On this island, flies are strongly associated with the toxic fruits of noni ( Morinda citrifolia ) and show a partial degree of pre-zygotic reproductive isolation. Here, I mine the nuclear and mitochondrial genomes and provide a full morphological description of this population. Only 29 nuclear sites (< 4 × 10 −7 of the genome) are fixed in this population and absent from 3 mainland populations and the closest relative D. santomea, but no mitochondrial or morphological character distinguish Mayotte flies from the mainland. This result indicates that physiological and behavioral traits may evolve faster than morphology at the early stages of speciation. Based on these differences, the Mayotte population is designated as a new subspecies, Drosophila yakuba mayottensis subsp. nov., and its strong potential in understanding the genetics of speciation and plant-insect interactions is discussed.